Pengaruh Fitur Layanan Shopee Paylater dan Kepuasan Pengguna Terhadap keputusan Pembelian Gen Z di Garut - Muhammad Akbar Surya Pratama; Hedi Cupiadi; Hilman Rismanto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The background of this research is based on the increasing use of Paylater services among Generation Z, who tend to prioritize convenience and satisfaction in online transactions. This study aims to examine the influence of Shopee Paylater service features and user satisfaction on purchasing decisions among Generation Z in Garut Regency. The research employs a descriptive and verification quantitative approach, utilizing primary data collected through questionnaires distributed to 110 Shopee Paylater users in Garut Regency. The sampling technique applied is non-probability sampling with a purposive sampling method. The independent variables in this study are service features and user satisfaction, while the dependent variable is purchasing decision. Data analysis was conducted using the Structural Equation Modelling–Partial Least Square (SEM-PLS) method. The results indicate that service features have a positive and significant influence on purchasing decisions. Additionally, user satisfaction also significantly affects purchasing decisions. Thus, the findings confirm that the better the service features and the higher the level of user satisfaction, the stronger the purchasing intention of Generation Z consumers in Garut Regency through Shopee Paylater.